2017
DOI: 10.1158/1538-7445.sabcs16-p6-11-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-11-04: The evaluation of ganitumab/metformin plus standard neoadjuvant therapy in high-risk breast cancer: Results from the I-SPY 2 trial

Abstract: Background: I-SPY 2 is a multicenter, phase 2 trial using response-adaptive randomization within biomarker subtypes to evaluate novel agents when added to standard neoadjuvant therapy for women with high-risk stage II/III breast cancer - investigational agent(I) +paclitaxel(T) qwk, doxorubicin & cyclophosphamide(AC) q2-3 wk x 4 vs. T/AC (control arm). The primary endpoint is pathologic complete response (pCR) at surgery. The goal is to identify/graduate regimens that have ≥85% Bayesian predictive probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Therapy 183 was 12 weeks in combination with paclitaxel and ganitumab, followed by 4 cycles (given every 2 or 3 184 weeks) of doxorubicin and cyclophosphamide. There was no benefit for adding ganitumab to 185 conventional cytotoxic chemotherapy in this trial as pathologic complete response rates were similar in 186 the ganitumab treated group compared to the control group (Yee, et al 2017). However, a preliminary 187 analysis of the data suggest metformin did not maintain glucose homeostasis.…”
Section: Monoclonal Antibodies 109mentioning
confidence: 79%
“…Therapy 183 was 12 weeks in combination with paclitaxel and ganitumab, followed by 4 cycles (given every 2 or 3 184 weeks) of doxorubicin and cyclophosphamide. There was no benefit for adding ganitumab to 185 conventional cytotoxic chemotherapy in this trial as pathologic complete response rates were similar in 186 the ganitumab treated group compared to the control group (Yee, et al 2017). However, a preliminary 187 analysis of the data suggest metformin did not maintain glucose homeostasis.…”
Section: Monoclonal Antibodies 109mentioning
confidence: 79%
“…The similar proportion of hypoglycemia AEs reported in the R/D/E and R/E arms suggest that this was not the case. Recently, the phase II Investigation of Serial Studies to Predict Your Therapeutic Response With Imaging And moLecular Analysis 2 (I-SPY-2) trial explored the IGF1R inhibitor ganitumab in combination with metformin in patients with stage 2/3 breast cancer and one of three tumor profiles: HER2-negative, hormone receptor-positive/HER2-negative, and hormone receptor-negative/HER2-negative [21]. Ganitumab/metformin did not meet the predefined criteria for graduation to a larger trial (≥85% bayesian predictive probability of success), nor did the addition of metformin stabilize HbA1c levels [21].…”
Section: Discussionmentioning
confidence: 99%
“…A short-term clinical trial in patients with breast cancer showed that, the tumor associated antigen CA15-3 significantly decreased after metformin treatment. However, since metformin may affect breast cancer in other ways as systemic changes in insulin metabolism, more trials should be performed in the future [ 117 ].…”
Section: Current Drugs Targeting the Hippo Pathway For Breast Cancmentioning
confidence: 99%